If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5x + 9) = -37 + 19 Reorder the terms: 3(9 + 5x) = -37 + 19 (9 * 3 + 5x * 3) = -37 + 19 (27 + 15x) = -37 + 19 Combine like terms: -37 + 19 = -18 27 + 15x = -18 Solving 27 + 15x = -18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 15x = -18 + -27 Combine like terms: 27 + -27 = 0 0 + 15x = -18 + -27 15x = -18 + -27 Combine like terms: -18 + -27 = -45 15x = -45 Divide each side by '15'. x = -3 Simplifying x = -3
| 6(-9-x)=-24 | | 2(2x)=32 | | -8(8x-6)=-6x-228 | | -2x+2=7x+65 | | 7m(2m-12)=0 | | -1+6x=-3x+8 | | 2(4x+2)+9x= | | 50/x=3 | | 90=3x+5x-6 | | ln(x)-ln(4)=0 | | (7+5x)-5x= | | ln(x)-on(4)=0 | | -25=5(3g+4) | | (9x+10)+(13-9x)= | | 3x^2-2y^2=1 | | z-38=-28 | | 12(5x+9)-11x= | | 25x+7(1.50)=10 | | X^5x=6 | | 5-5x-x=53 | | -1+5x-7x=3 | | 8.4254+.6018R=R | | 6(x+2)=5(x+4) | | 9x^4-19x^2-2=0 | | -3+x=6n+22 | | -30x+12(x-1)=24x+200 | | 5x-y=30(3) | | 5a-5ab= | | 2x=x+14x | | A^2+11a=-30 | | 3+0.4n= | | -11+51=-4(x+5) |